梁智强电影再现的老人、小孩与中产阶级人士 = The representation of the elderly, the young and the middle class Singaporeans in Jack Neo’s movies - 黄毓薇 Wong, Yi Wei (2010)
本文的研究对象是梁智强电影。第一章将介绍梁智强以及梁智强电影，研究目的与方法。然后通过梁智强电影再现的三种人物，即“老人”、“小孩”与“中产阶级人士”看梁智强电影如何试图形塑新加坡社会对于这三种人的看法以及初涉其背后的意义。 This article shall analyse Jack Neo’s movies. The first chapter is an introduction of Jack Neo and his movies, the purpose of this research and the method used. Then, through the representation of the elderly, the young and the middle class Singaporeans, an analysis is made to see how Jack Neo’s movies attempt to shape Singapore’s perception towards these groups of people and shall touch a bit on the motivation behind it.